ARTISTIC PERCEPTION AND ITS IMPORTANCE IN THE FORMATION OF AESTHETIC CONSCIOUSNESS OF FUTURE TEACHERS - Varnyak І.С. (Pedagogy of Higher and Secondary Education, 2022)
The article s reveal the problem of artistic perception lite necessary condition of effective aesthetic education and it is a significant aspect of development of aesthetic consciousness of personality.